TRAIL Deficiency Contributes to Diabetic Nephropathy in Fat-Fed ApoE(-/-) Mice - Cartland, Siân P. (Public Library of Science, 2014)
BACKGROUND: We recently demonstrated that TNF-related apoptosis-inducing ligand (TRAIL) is protective of diet-induced diabetes in mice. While TRAIL has been implicated in chronic kidney disease, its role in vivo in diabetic nephropathy is not clear. The present study investigated the role of TRAIL in the pathogenesis of diabetic nephropathy using TRAIL(-/-)ApoE(-/-) mice. METHODS: TRAIL(-/-)ApoE(-/-) and ApoE(-/-) mice were fed a high fat diet for 20 w. Plasma glucose and insulin levels were assessed over 0, 5, 8 and 20 w. At 20 w, markers of kidney function including creatinine, phosphate, calcium and cystatin C were measured. Changes in mRNA expression of MMPs, TIMP-1, IL-1β and IL-18 were assessed in the kidney. Functional and histological changes in kidneys were examined. Glucose and insulin tolerance tests were performed. RESULTS: TRAIL(-/-)ApoE(-/-) mice had significantly increased urine protein, urine protein:creatinine ratio, plasma phosphorous, and plasma cystatin C, with accelerated nephropathy. Histologically, increased extracellular matrix, mesangial expansion and mesangial cell proliferation in the glomeruli were observed. Moreover, TRAIL(-/-)ApoE(-/-) kidneys displayed loss of the brush border and disorganisation of tubular epithelium, with increased fibrosis. TRAIL-deficient kidneys also had increased expression of MMPs, TIMP-1, PAI-1, IL-1β and IL-18, markers of renal injury and inflammation. Compared with ApoE(-/-) mice, TRAIL(-/-)ApoE(-/-) mice displayed insulin resistance and type-2 diabetic features with reduced renal insulin-receptor expression. CONCLUSIONS: Here, we show that TRAIL-deficiency in ApoE(-/-) mice exacerbates nephropathy and insulin resistance. Understanding TRAIL signalling in kidney disease and diabetes, may therefore lead to novel strategies for the treatment of diabetic nephropathy.